Bacterial diversity in bovine rumen by metagenomic 16S rDNA sequencing and scanning electron microscopy - Jesus, Raphael Barbetta de; Omori, Wellington Pine; Lemos, Eliana Gertrudes de Macedo; Souza, Jackson Antônio Marcondes de (Acta Scientiarum. Animal Sciences, 2015)
The bacterial diversity by 16S rDNA partial sequencing and scanning electron microscope (SEM) of the rumen microbiome was characterized. Three Nellore bovines, cannulated at the rumen, were utilized. Liquid and solid fractions from the rumen content were processed for the extraction of metagenomic DNA and later 16S rDNA amplicons were utilized to construct the WGA library for further clone sequencing. Data were analyzed by MEGA and MOTUR (University of Michigan) softwares. Approximately 97.96% of operation taxonomic units (OTUs) were related to Bacteriodetes phylum and 2.04% of sequences were affiliated to Firmicutes phylum. In the case of Bacteriodetes, the great part of sequences (47.96%) was attributed to Prevotella genus. Bacteroidetes phylum was predominant in rumen content and the Prevotella genus was the most abundant, including diverse species related to this taxon. The bacterial morphological diversity associated to plant fibers was detected by SEM and showed its role in plant biomass deconstruction beyond the detection of microbiological interactions that involved protozoa